European Union Regulations in AI Issues - Mateescu, Florina (Didactica Danubiensis, 2022)
Technology is always developing, so many fields are constantly changing under its auspices. In the study we propose, we want to highlight the legal importance of artificial intelligence, but especially its development mode, referring also to the legal responsibility it implies. We will use the legal source - the European norm - to highlight the topicality of our theme. The methods that will help us in structuring the paper are: the logical method, the descriptive method, the sociological method. The novelty of the study will consist in the analysis and understanding of European provisions, with concrete applicability. We want the chosen topic to arouse the interest of all legal experts, as well as novices in the field and not only that.